Too Big to Prevail: The Paradox of Power in Coalition Formation - Changxia Ke; Florian Morath; Anthony Newell; Lionel Page (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In standard coalition games, players try to form a coalition to secure a prize and a coalition agreement specifies how the prize is to be split among its members. However, in practical situations where coalitions are formed, the actual split of the prize often takes place after the coalition formation stage. This creates the possibility for some players to ask for a renegotiation of the initial split. We predict that, in such situations, a player can suffer from being “too strong”. Our experimental results confirm that, when the actual split of the prize is delayed, a player's strength can turn into a strategic disadvantage: a greater voting power in forming a winning coalition is undermined by the threat of being overly powerful at the stage when a split is determined. This result is relevant to many real world situations where “too strong” players find it paradoxically hard to partner with weaker players to win the game.
Keywords: C71; C92; D72; D74; 330; Shapley Value; (non) binding agreement; balance of power; communication